The XQR-30 metal absorber catalogue: 778 absorption systems spanning 2 ≲ z ≲ 6.5. Issue 1 (7th March 2023) - Davies, Rebecca L; Ryan-Weber, E; D'Odorico, V; Bosman, S E I; Meyer, R A; Becker, G D; Cupani, G; Bischetti, M; Sebastian, A M; Eilers, A-C; Farina, E P; Wang, F; et al.
ABSTRACT: Intervening metal absorption lines in the spectra of z ≳ 6 quasars are fundamental probes of the ionization state and chemical composition of circumgalactic and intergalactic gas near the end of the reionization epoch. Large absorber samples are required to robustly measure typical absorber properties and to refine models of the synthesis, transport, and ionization of metals in the early Universe. The Ultimate XSHOOTER legacy survey of quasars at z ∼ 5.8–6.6 (XQR-30) has obtained high signal-to-noise spectra of 30 luminous quasars, nearly quadrupling the existing sample of 12 high quality z ∼ 6 quasar spectra. We use this unprecedented sample to construct a catalogue of 778 systems showing absorption in one or more of Mg ii (360 systems), Fe ii (184), C ii (46), C iv (479), Si iv (127), and N v (13) which span 2 ≲ z ≲ 6.5. This catalogue significantly expands on existing samples of z ≳ 5 absorbers, especially for C iv and Si iv which are important probes of the ionizing photon background at high redshift. The sample is 50 per cent (90 per cent) complete for rest-frame equivalent widths W ≳ 0.03 Å (0.09 Å). We publicly release the absorber catalogue along with completeness statistics and a python script to compute the absorption search path for different ions and redshift ranges. This data set is a key legacy resource for studies of enriched gas from the era of galaxy assembly to cosmic noon, and paves the way for even higher redshift studies with JWST and 30 m-class telescopes.